Mitologi dan Agama dalam Masyarakat Modern - Lina, Ismir (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
The elimination of myths and religion in modern society has resulted in the despiritualization of religion and the demoralization of spirituality. The predominantly materialistic and positivistic approach of science has created a spiritual and humanitarian crisis, perceiving nature as a lifeless mechanical entity. This perspective contradicts the beliefs of our ancestors who revered nature as a living entity akin to humans. This study elucidates the relationship between myths, religion, and science through the perspectives of Karen Armstrong and Jalaluddin Rumi. Armstrong asserts that myths and religious laws are not true due to their alignment with metaphysical, scientific, or historical realities, but because of their life-affirming nature. Rumi, in his view, illustrates that knowledge that penetrates the soul requires spirit and emanates from the sublime realm beyond reason and words. This perspective amalgamates myths, religion, and science into a unity that respects spiritual existence and regards nature as something far beyond the comprehension of ordinary human beings.AbstrakPenyingkiran mitos dan agama dalam masyarakat modern telah menyebabkan dispiritualisasi agama dan demoralisasi spiritual. Ilmu pengetahuan yang cenderung materialistik dan positivistik telah menciptakan krisis spiritual dan kemanusian, menganggap alam sebagai mesin mekanis tanpa kehidupan. Pandangan ini bertentangan dengan kepercayaan leluhur kita yang menghormati alam sebagai entitas bernyawa, seperti manusia. Kajian ini mendeskripsikan hubungan antara mitos, agama, dan ilmu pengetahuan melalui perspektif Karen Armstrong dan Jalaluddin Rumi. Armstrong menyatakan bahwa mitos dan hukum agama bukanlah benar karena kesesuaiannya dengan realitas metafisik, ilmiah, atau historis, tetapi karena sifatnya yang menghidupkan. Rumi, dalam pandangannya, menggambarkan bahwa pengetahuan yang mencapai jiwa memerlukan ruh dan berasal dari alam yang agung di luar nalar dan kata-kata. Pandangan ini menggabungkan mitos, agama, dan ilmu pengetahuan sebagai satu kesatuan yang menghormati keberadaan spiritual dan memandang alam sebagai sesuatu yang jauh melampaui pemahaman manusia biasa.